The complex P2X7 receptor/inflammasome in perivascular fat tissue of heavy smokers. (20th January 2014) - Rossi, Chiara; Santini, Eleonora; Chiarugi, Massimo; Salvati, Antonio; Comassi, Mario; Vitolo, Edoardo; Madec, Stephanie; Solini, Anna
Abstract Objective Smoking is a recognized cardiovascular risk factor. Perivascular visceral adipose tissue (PVAT) is a source of inflammatory molecules, thus contributing to atherosclerosis progression. The P2X7 receptor (P2X7R)‐inflammasome complex, crucial in determining IL‐1β and IL‐18 release, participates in this scenario. We evaluated whether smoking might affect the PVAT inflammatory phenotype and explored the putative role of the axis P2X7R‐inflammasome in this picture. Subjects and Methods TNFα, IL‐6, RBP4, MCP‐1, as well as P2X7R and inflammasome components NLRP3, ASC, caspase‐1 and IL‐1β and IL‐18 expression was determined in adipocytes isolated by PVAT of healthy smokers (Smok) and nonsmokers (No‐Smok) subjects. Plasma and culture medium levels of these cytokines were also determined. Results Perivascular adipose tissue of Smok had a higher expression of P2X7R and inflammasome components; via P2X7R activation, it released more IL‐1β and IL‐18, whose serum levels were also higher in Smok than in No‐Smok. Linear correlations of NLRP3 with P2X7R and IL‐18 expression and release emerged. Smok also had a higher PVAT expression of the chemotactic factor MCP‐1. However, no difference was observed in the PVAT expression of genes more strictly related to insulin resistance, like TNFα, RBP4, IL‐6; this was coupled with similar plasma levels of TNFα and RBP4 in the two groups. Conclusion Smoking contributes to the pro‐inflammatory status of the PVAT by enhancing expression and activity of the P2X7R‐inflammasome complex; the effect on adipocytokines more related to insulin resistance and metabolic abnormalities appears trivial.